The new governance of French education? - Cole, Alistair (2001)
This article contributes to ongoing debates in comparative public administration through exploring the governance paradigm in the unfavourable empirical terrain of French education. After identifying potentially relevant features of governance, we investigate changing patterns of policy-making in French education at macro, meso and micro levels. Extrapolating research findings from extensive interviews and participant observation at ministerial meetings, we conclude the existence of a French-style governance that operates within distinctive ideational and institutional environments and interest structures. The article emphasizes the importance of historical and institutional traditions in framing the available pathways of governance. - Reproduced
Keywords: Education - France; Public administration - France; Education